Antipsychotics, Hypothermia, Undressing, and Death - Mary V Seeman (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
One of the lesser-known adverse effects of antipsychotic medication is hypothermia, a significant and protracted plunge in body temperature. Known risk factors are older age and exposure to a new-for-the-person antipsychotic drug. Hypothermia impairs cognitive function, often resulting in a delirium that can paradoxically induce the prescription of escalating doses of the offending drug. As hypothermia increases, the subjective experience of the person may be one of overwhelming heat that can lead to the person shedding protective clothing, an action that can precipitate death.